Shelf life Extension of Whole and Steaks of Rohu (Labeo rohita) by Gamma Irradiation - S.B., Warrier; S., Panchavarnam; K., Manisha; S., Basu; V., Venugopal (Fishery Technology, 2025)
Fresh rohu were procured from the local market and packed in polyethylene pouches and were subjected to gamma irradiation as whole or steaks at a dose of 0, 1 or 2 kGy. The treated fish and steaks were stored under ice. At periodic intervals, quality of the fish was determined by sensory, microbiological and chemical parameters. The unirradiated whole fish and steaks were acceptable up to 14 and 20 days in comparison to a storage life of 28 and 32 days for the respective samples irradiated at 1 kGy. Irradiation of whole fish at 2 kGy gave a shelf life of 35 days. The extent of lipid oxidation due to irradiation was not significant and had no effect on sensory quality of the ice-stored fish.